Impact of endoscopic ultrasound‐guided fine‐needle biopsy on the diagnosis of subepithelial tumors: A propensity score‐matching analysis. Issue 2 (3rd October 2018) - Inoue, Tadahisa; Okumura, Fumihiro; Sano, Hitoshi; Mizushima, Takashi; Tsukamoto, Hironobu; Fujita, Yasuaki; Ibusuki, Mayu; Kitano, Rena; Kobayashi, Yuji; Ishii, Norimitsu; Ito, Kiyoaki; Yoneda, Masashi
Abstract : Background and Aim: Immunohistological evaluations are essential for diagnosing subepithelial tumors (SET). However, endoscopic ultrasound‐guided sampling using fine‐needle aspiration (FNA) needles is limited in its ability to procure core tissue for immunostaining. Fine‐needle biopsy (FNB) needles may mitigate this limitation. The present study aimed to examine the efficacy of FNB needles for procuring samples that enable the diagnosis of SET. Methods: One hundred sixty patients were included in the study and separated into those whose samples were obtained using FNB needles (FNB group) and those whose samples were procured using FNA needles (FNA group). Groups were compared regarding the conclusive diagnosis rate and unwarranted resection rate. Propensity score matching was introduced to reduce selection bias. Results: Rates at which conclusive diagnoses were reached through adequate immunohistological evaluations were 82% and 60% in the FNB and FNA groups, respectively; this difference was significant ( P = 0.013). Unwarranted resection rate was significantly lower in the FNB group (2%) than in the FNA group (14%; P = 0.032). Multivariate analyses showed that lesions ≤20 mm were a significant risk factor for lower conclusive diagnosis rates following the use of FNB needles ( P = 0.017). Conclusions: Fine‐needle biopsy needles can be useful for obtaining samples that facilitate the diagnosis of SET and for avoiding unwarranted resections. However, FNB needles may be less advantageous for small SET.